(untitled) (Discourse of Law and Administration, 2023)
The article attempts to define what is meant by the concept of ‘legal capacity’ in light of article 86 of the Polish Notary Law. Based on an analysis of the jurisprudence and doctrine, a conclusion has been formulated that, in fact, this notion differs significantly from the general notion of legal capacity as defined in the Polish Civil Code. Indeed, according to the dominant direction of functional interpretation, a distinction is made between ‘legal capacity sensu stricto’ – i.e. within the meaning of the Civil Code, and ‘legal capacity sensu largo’ – i.e. within the meaning of Article 86 of the Law on Notaries. The latter concept refers not so much to the objective formal circumstances concerning a party to a notarial action, such as age or incapacitation, but rather to the subjective ability to make a conscious and free decision to formulate a declaration of intent. The reasons for the formation of this line of interpretation are furthermore presented against a broad historical and comparative background. As part of the concluding remarks, several conclusions have been formulated as to the possible need to modify Article 86 of the Notary Law in its current wording, due to interpretation doubts related to its drafting. Based on dogmatic, historical and comparative arguments, a postulate was formulated to repeal this provision in its entirety. This is supported not only by its defective drafting, but also by the fact that a legal norm of similar content can be interpreted from other provisions of the Polish Notary Law.